2020
DOI: 10.1111/jpy.12976
|View full text |Cite
|
Sign up to set email alerts
|

How light and biomass density influence the reproduction of delayed Saccharina latissima gametophytes (Phaeophyceae)

Abstract: Kelp life‐cycle transitions are complex and susceptible to various (a)biotic controls. Understanding the microscopic part of the kelp's lifecycle is of key importance, as gametophytes form a critical phase influencing, among others, the distributional limits of the species. Many environmental controls have been identified that affect kelp gametogenesis, whose interactive effects can be subtle and counterintuitive. Here we performed a fully factorial experiment on the (interactive) influences of light intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Biomass density (Ebbing et al. 2020) or in this study culture age could influence the reproduction of multiannual delayed gametophyte cultures in more profound ways than it would influence the reproduction of newly formed gametophyte cultures. This is because the prolonged periods of vegetative growth not only increase the age and biomass density of multiannual delayed gametophyte cultures, but may also change genetic diversity and sex ratio of the cultures if genotypes and sexes have different vegetative grow rates (e.g., see Destombe and Oppliger 2011).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Biomass density (Ebbing et al. 2020) or in this study culture age could influence the reproduction of multiannual delayed gametophyte cultures in more profound ways than it would influence the reproduction of newly formed gametophyte cultures. This is because the prolonged periods of vegetative growth not only increase the age and biomass density of multiannual delayed gametophyte cultures, but may also change genetic diversity and sex ratio of the cultures if genotypes and sexes have different vegetative grow rates (e.g., see Destombe and Oppliger 2011).…”
Section: Discussionmentioning
confidence: 79%
“…The transitions between these life phases are controlled by abiotic and biotic environmental factors (Lüning and Dieck 1989), hereafter described as life cycle controls (Ebbing et al. 2020). Extensive studies on life cycle controls for newly formed Saccharina latissima gametophytes have identified the following as the main drivers: light intensity (Hsiao and Druehl 1971, Bolton and Levitt 1985), temperature (Lüning and Neushul 1978, Morita et al.…”
mentioning
confidence: 99%
“…Putative density-associated nutrient deficiency is sometimes offered as an explanation [23,30]. However, [21] showed that the interaction between gametophyte density and reproduction was not due to nutrient availability but could also directly be correlated with the density of the culture itself. The next logical step was to assess whether male or female gametophyte biomass was instrumental to this apparent correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Ripe Saccharina latissima sorus of 6 individuals from Leknesund, Norway (61.212994, 4.896644 • E) and Alaria esculenta sorus of 8 individuals from Fuhreholmen, Norway (61.043292, 4.868790 • E), were collected and pooled in 2016. The release of zoospores was performed in the Netherlands, using a standard extraction protocol (protocol of [21], similar to earlier methods described by [22,23]). Zoospores were isolated from the culture to set up clean clonal cultures, separating the sexes.…”
Section: Cell Culture and Maintenancementioning
confidence: 99%
“…This results in the spatiotemporal separation of meiosis and fertilization, with somatic development occurring at both the haploid and diploid stages (Bell et al 1997). The transitions between these life phases is controlled by abiotic and biotic environmental factors (Lüning and Dieck 1989), hereafter described as life cycle controls (Ebbing et al 2020). Extensive studies on life cycle controls for newly formed S. latissima gametophytes have identified the following as the main drivers: light intensity (Hsiao and Druehl 1971;Bolton and Levitt 1985), temperature (Lüning and Neushul 1978;Morita et al 2003), nutrients (Harries 1932;Martins et al 2017), daylength (Choi et al 2005;Martins et al 2017), and initial gametophyte density (Choi et al 2005;Carney and Edwards 2010;Ebbing et al 2020).…”
Section: Introductionmentioning
confidence: 99%